STRATEGI PEMERINTAH DESA DALAM PEMBERDAYAAN EKONOMI MASYARAKAT (Studi Pemberdayaan Melalui Bumdes Bangun Mandiri Bekiung - Langkat) - Witri Niyarsih; Agus Purwanto (Ekonomika : Jurnal Ekonomi dan Pembangunan, 2023)
This research aims to determine the village government's strategy in empowering the community's economy and the obstacles through BUMDES Bangun Mandiri Dfesa Bekiung, Kuala District. Qualitative research with questionnaire instruments, interviews and document studies. The informants in this research included the Village Head, Director and Treasurer of BUMDES, as well as the community. Research findings 1) the village government's strategy in empowering the community's economy is carried out by providing savings and loan business capital loans, a profit sharing system scheme. 2) providing entrepreneurial assistance and training by BUMDES administrators to the community, as well as encouraging community participation to help advance the business unit. 3) the obstacles include the lack of capital owned by BUMDES, the lack of skills and expertise of human resources in managing BUMDES and institutional management which is still not running optimally and the lack of community participation.